An effective seeding method for restoring the surfgrass Phyllospadix japonicus using an aartificial reef - Park, Jung-Im; Son, Min Ho; Kim, Jeong Bae; Lee, Kun-Seop (Ocean science journal, 2014)
Phyllospadix japonicus is an abundant surfgrass that thrives mainly along the exposed rocky shores of Northeastern Asia. On the eastern coast of Korea, surfgrass populations have been adversely affected by increasing human pressures. We developed a seeding method using an artificial reef for the restoration of P. japonicus . In January 2005, we planted P. japonicus seeds on the lower part of coarse hemp-plant brush that was embedded densely on the concave surface on the top of artificial reefs. The reefs were then installed on an exposed rocky shore. To evaluate the feasibility of this seed-based surfgrass restoration technique, we monitored the seedling/shoot density and morphological characteristics of the shoots over a 2-year period. Seedlings began to emerge within the first month after seeding, reaching densities of up to 275.0 shoots m -2 by April 2005. After an initial decline, shoot density increased through the production of lateral shoots, and densities of up to 997.1 shoots m -2 were observed by the end of the experiment. Shoot height, the number of leaves, and leaf width rapidly increased during the first year after seeding, whereas the number of rhizome internodes and rhizome length rapidly increased during the second year. The P. japonicus shoots exhibited approximately 63.4 mm of rhizome elongation during the study period. Because seeded P. japonicus on the artificial reefs were successfully established at the study site, this seeding method using an artificial reef may offer an effective approach to restoring surfgrass habitat.